The Mosque and Masjid Waqfs of Antep According to the Judicial Registers (1880-1900) - Kundakçi, Sibel (Gaziantep University Journal of Social Sciences, 2014)
Waqf is a foundation providing actualization of religional, cultural, social and economical activities according to service areas in the cities and the rural areas where they are established. As a result of this, the city life of Ottoman had contiuned its vividness in every period. In this study, it will be worked to present the mosque and the masjid waqfs of Antep between the years 1880 and 1900 according to the judicial (şer’iyye) registers of Antep

Vakıf, kuruldukları şehir ve kırsal alanda hizmet alanlarına göre dinî, kültürel, sosyal ve ekonomik faaliyetlerin gerçekleştirilmesini sağlayan bir müessesedir. Bu sayede, özellikle Osmanlı şehir yaşamı her dönem canlılığını korumuştur. Bu çalışmada, 1880 ve 1900 yılları arasında Antep’te bulunan cami ve mescit vakıfları Antep şer’iyye sicillerine göre değerlendirilmeye çalışılacaktır
Keywords: Antep; waqf; judicial (şer’iyye) registers; mosque; masjid; Antep; vakıf; şer’iyye sicilleri; câmii; mescit; 11. Sustainability